On Koreanness and the limits of the National Cinema. Transnational-Korean Adoptees in non-Korean Cinema - Rud, Lucía (2025)
The Republic of Korea (hereafter, Korea) is one of the world's highest per capita countries for transnational adoption, with over 200,000 Korean children adopted from Western countries, particularly the United States, and were raised predominantly by white families. This topic, not without controversy, has been depicted in 27 contemporary non-Korean films, several of them directed by the adoptees themselves.   This article aims to (1) provide a systematic survey of these films; (2) analyze how they negotiate identity, belonging, and national narratives; and (3) examine their place within the emerging framework of “Korean diasporic cinema.” It argues that these films not only make visible marginalized adoptee experiences but also challenge and reframe dominant conceptions of Koreanness through transnational and adoptive perspectives.